PEMBELAJARAN IPS BERBASIS PENGETAHUAN DAUR HIDUP MANUSIA KALIMANTAN SEBAGAI KEARIFAN LOKAL SISWA KELAS IV MI SULAMUL ULUM SUNGAI KUNJANG SAMARINDA - Euis Kusuma Rini (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
This study aims to (1) obtain empirical data on the implementation of knowledge-based learning lifecycle of Kalimantan as an indigenousin the fourth grade students of MI Sulamul Ulum Sabilal Muhtadin Sungai Kunjang Samarinda Ulu , and (2) obtain empirical data on the level of religiosity of the fourth gradestudents before and after learned the life cycle of human knowledge based Kalimantan as local wisdom. This research is a pre-experimental one group pre-post test design. The respondents were students of class IV MI Sulamul Ulum Sabilal Muhtadin Sungai Kunjang Samarinda, totaling 39 people. Research variables consist of materials of human life cycle-based Kalimantan cultur(X), and religiosity (Y). The data in this study were collected using a questionnaire. Data were analyzed with descriptive statistics using SPSS 20, and presented in tables and diagrams. The results are as follows:(1) implementation of thesocial studiesstudy done with the material that comes from the utilization of natural resources for life-cycle ceremonies and customs that still practiced by the Sungai Kunjang Samarinda district, the customs when the human still in the womb, when human birth,adolescence, marriage, and death. Social studies learning conducted with games crosswords and scramble. (2) Religiosity students are in high and very high categories. At the time of the pretest, students with high category as 6 people (29%) reduced the number to 2 people (5.2%) at posttest. Decrease the number of students for the high category is accompanied by an increase in the number of students with very high category at the pretest as many as 32 people (71%) increased to 37 people (94.8%) at posttest. The mean score of religiosity of students before and after studying knowledge basedthe life cycle of Kalimantan cultureincreased by 3.47%.